Competitive dynamics of telecommunications markets in South Africa, Tanzania, Zambia, and Zimbabwe - Genna Robb; Anthea Paelo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Low levels of broadband penetration combined with poor quality of services present a challenge to growth and development in the Southern African Development Community (SADC). This paper performs a comparative analysis of the competitive dynamics of telecommunications markets in four SADC countries and relates this to outcomes for consumers. From a mobile perspective, a common theme is that while entrants have attracted subscribers, they have struggled to grow revenues and compete effectively due to tariff-mediated network effects and the high cost of building a network. Fixed markets are underdeveloped and highly concentrated. Access to fixed and mobile infrastructure is a challenge, in spite of regulations mandating access in most countries. Where mobile money has taken off, this has sometimes exacerbated network effects and enhanced the market power of incumbents, although the development of interoperability in some countries has had a positive impact. The findings suggest that regulation has often been ineffective in facilitating competition in telecommunications markets in SADC.
Keywords: L1; L51; L96; 330; competition; fixed and mobile infrastructure; interoperability; Southern African Development Community; telecommunications